2020
DOI: 10.1002/bmc.4963
|View full text |Cite
|
Sign up to set email alerts
|

Nine absorbed components pharmacokinetic of raw and processed Moutan Cortex in normal and blood‐heat and hemorrhage syndrome model rats

Abstract: Raw Moutan Cortex (RMC) and Processed Moutan Cortex (PMC) have a long history of use in China and other Asian countries. In this study, a rapid and accurate ultra‐high‐pressure liquid chromatography coupled with diode array detector (UHPLC–DAD) method was developed and validated for the simultaneous determination of nine absorbed compounds of RMC/PMC. After extraction by protein precipitation with methanol from plasma, the analytes were separated on an Acquity UPLC® BEH Shield RP18 column (2.1 × 100 mm, 1.7 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…However, the concentration of the second peak did not increase significantly in group NEO + EO, so that the t max value was significantly longer in group NEO. A similar phenomenon had been reported before (Ye et al, 2020), where the concentration of the second peak was significantly higher. The conversion between components may be the reason for the second peak after the oral administration.…”
Section: Resultssupporting
confidence: 90%
“…However, the concentration of the second peak did not increase significantly in group NEO + EO, so that the t max value was significantly longer in group NEO. A similar phenomenon had been reported before (Ye et al, 2020), where the concentration of the second peak was significantly higher. The conversion between components may be the reason for the second peak after the oral administration.…”
Section: Resultssupporting
confidence: 90%
“…However, Cortex Moutan Carbon, the Processed product of Moutan Cortex (PMC), had the opposite effect of cooling blood and hemostatic. Our last article research found that PMC may promote the absorption of 5-HMF and inhibit oxypaeoniflorin, quercetin and 3, 8-Dihydroxy-2- methylchromone absorption in Blood-Heat and Hemorrhage Syndrome Model rat (BHH) as compared with the normal rats [ 37 ]. The absorption of three components (3, 8-dihydroxy-2-methylchromone, benzoic acid, quercetin) was promoted and 5-HMF was inhibited in BHS-RMC.…”
Section: Discussionmentioning
confidence: 99%
“…The chromatography experiment was carried out using UPLC system (Thermo Fisher Scientific, USA). Chromatographic conditions were according to the paper published by our research group [ 37 ]. Column: Acquity UPLC ® BEH Shield RP 18 Column (2.1 mm × 100 mm, 1.7 μm, Waters, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…UHPLC-MS/MS has been widely focused on the preclinical analytical application research and pharmacokinetics during the last decade [ 26 ]. Small particle sizes in columns in UHPLC systems play a crucial role in the process of separation, which can not only increase separation efficiency and sensitivities but also reduce the chromatographic run time [ 27 ].…”
Section: Introductionmentioning
confidence: 99%